Watching the sleeper in Macbeth. (2nd July 2016) - Simpson-Younger, Nancy
Abstract : This paper contends that the act of watching a sleeper in the early modern period carried ethical implications. When a "watcher" stayed awake near a sleeper, it was his or her job to safeguard that person's health, identity, and well-being. This behaviour not only recognized the common humanity of the sleeper and the watcher; it preserved social order, because the identity of each person was wrapped up in the predictable, preserved identities of those nearby. When a character like Macbeth violates the ethics of the watch by killing the sleeping Duncan, then, he not only destabilizes a monarchy. Instead, he also fractures the passible network of human connections that allows legible individual identities to exist. In this light, Macbeth can be read as a case study of the consequences of violating the watch: ethical systems crumble, sleepwalkers cannot be effectively diagnosed or labelled, and even the belief in a benevolently watching heaven falters. By exploring the violation of the watch, in other words, Shakespeare asks if individual human identities can be maintained in the absence of a passible ethical economy–and he strongly implies that they cannot.